The distinct roles of IL-37 and IL-38 in non-small cell lung carcinoma and their clinical implications - Zhang, Jiwei; Wise, Steven G.; Zuo, Shunqing; Bao, Shisan; Zhang, Xufeng (Frontiers in Immunology, 2025)
Lung cancer, a significant global health challenge, is primarily classified into non-small cell lung cancer (NSCLC) and small cell lung cancer. Despite advancements in targeted therapies and immunotherapies, NSCLC outcomes remain poor, with low five-year survival rates. Given the lung’s constant exposure to the environment and the presence of mucosal-associated lymphoid tissues, immunity plays a crucial role in NSCLC development. Immune checkpoint inhibitors (ICIs) targeting PD-1/PD-L1 have shown promise. However, adverse immune events limit their efficacy. This review highlights the contrasting roles of IL-37 and IL-38 in NSCLC pathogenesis. IL-37, an anti-inflammatory cytokine, suppresses tumour growth. It achieves this by modulating macrophage polarization and dendritic cell maturation. Correlations between intra-tumoral IL-37 expression and improved survival suggest a protective role in NSCLC. This may be mediated through VEGF inhibition and immune regulation. Conversely, IL-38, while anti-inflammatory in certain contexts, exhibits a pro-tumorigenic role in NSCLC. IL-38 enhances tumour progression by increasing pro-inflammatory cytokine secretion and facilitating immune evasion, potentially through NF-κB signalling. Notably, IL-38 negatively regulates IL-37, further promoting tumorigenesis. Emerging data suggest that IL-37 has therapeutic potential in inhibiting NSCLC metastasis and supporting immune modulation. In contrast, IL-38 presents a potential target for mitigating pro-inflammatory microenvironment effects. The distinct roles of these cytokines emphasize the complex immune dynamics in NSCLC. Further exploration of their molecular mechanisms and therapeutic implications is warranted. Targeting IL-37 and IL-38 may offer novel strategies for enhancing NSCLC treatment outcomes